2015
DOI: 10.1016/j.fsigss.2015.09.067
|View full text |Cite
|
Sign up to set email alerts
|

Reference gene study for forensic body fluid identification

Abstract: Reference genes are used in forensic body fluid identification studies to normalise data generated during gene expression experiments. The use of reference genes improves the reliability of qRT-PCR. In this study, 10 most common reference genes UCE, TEF, GAPDH, 18S rRNA, ACTB, B2M, B-Actin, OAZ1, RPS 29 and S15 widely used in forensic body fluid identification studies were selected from relevant literature and qPCR efficiency and sensitivity of all the reference genes was tested using SYBR Green detection. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
1
1
1
Order By: Relevance
“…The genes selected include GAPDH, 18S rRNA, β-Actin, OAZ1, S15, ACTB, B2M, RPS29, TEF and UCE. The results showed that ACTB, B2M, RPS29, TEF and UCE passed the reaction efficiency test using SYBR Green and were further detectable in all the body fluids up to 25 pg using Taqman probes (Afolabi et al, 2015). However, as shown in the present study, TEF did not demonstrate high sensitivity as other markers, especially on semen, blood and menstrual blood.…”
Section: Resultscontrasting
confidence: 50%
“…The genes selected include GAPDH, 18S rRNA, β-Actin, OAZ1, S15, ACTB, B2M, RPS29, TEF and UCE. The results showed that ACTB, B2M, RPS29, TEF and UCE passed the reaction efficiency test using SYBR Green and were further detectable in all the body fluids up to 25 pg using Taqman probes (Afolabi et al, 2015). However, as shown in the present study, TEF did not demonstrate high sensitivity as other markers, especially on semen, blood and menstrual blood.…”
Section: Resultscontrasting
confidence: 50%
“…Additionally, in an EDNAP study, B2M was the only reference gene detected in challenging (trace) samples (Haas et al, 2015). B2M was the most stable in a small study by Afolabi, Roeder, Iyengar, and Hadi (2015) where a panel of reference genes was assessed for their efficiency and sensitivity across blood, menstrual fluid, vaginal material, saliva, and semen. However, B2M has been shown to be up‐ or downregulated in individuals with tumors, and when the immune system is compromised (Larsson et al, 1994; Momburg & Koch, 1989).…”
Section: Rt‐qpcr For Body Fluid Identificationmentioning
confidence: 99%
“…Специальных требований для базовой линии не существует, хотя условия ПЦР стараются подгонять таким образом, чтобы высота минимального сигнала была не ниже 150RFU, хотя некоторые опуска-ют и до 50RFU [25]. Затруднения в точности установки базовой линии, в частности, обусловлены некоторой лабильностью экспрессии генов «домашнего хозяйства» (ГДХ), амплификация которых служит своеобразным внутренним контролем [26]. Было показано, что компо-зиция их экспрессии зависит от типа тканей, поэтому в разных модификациях панели «CellTyper» и аналогов может присутствовать разный состав в виде двух-трёх типов ГДХ, которые специфично проявляются в том или ином типе тканей [8,23].…”
Section: капиллярный электрофорезunclassified